Characterization of B-glukosidase Enzyme from Vanilla Bean - Dwi Setyaningsih; Maggy T Soehartono; Anton Apriyantono; Ika Mariska (Jurnal Teknologi dan Industri Pangan, 2007)
The Indonesian natural vanilla is know for having a unigue woody, smooky, and phenolic flavor. Development of the aroma and flavor vanilla was formed by the action of a hydrolytic enzyme B-glucosidase on glucovanillin. The objective of this research was to characterize vanilla B-glucosidase. The vanilla B-glucosidase activity was increased by detergent. The enzyme was found as heat labile. Scalding should be conducted at 400C for 2-3 minutes. The result from B-glucosidase activity in each part of vanilla and microscopic analisis of vanilla bean slice showed that the highest B-glucosidase activity and vanillin concentrations were found in the seed funicles and placental tissue the of vanilla bean. The activity of vanilla B-glucosidase was optimum at pH 6,0, and temperature of 400C, found as and activation energy was 5,78 kcal/mole. After 44 minutes incubation time at 400C. The activity was reduced down to 10%. The apparent of moleculer weight was 100-400 kDa according to gel setration (Sephacryl S-300) analysis. Key words : Vanilla planifolia, B-glucosidase